2018
DOI: 10.1007/s11011-018-0234-2
|View full text |Cite|
|
Sign up to set email alerts
|

Indian Ginseng (Withania somnifera) supplementation ameliorates oxidative stress and mitochondrial dysfunctions in experimental model of stroke

Abstract: Stroke is an increasingly prevalent clinical condition and second leading cause of death globally. The present study evaluated the therapeutic potential of Indian Ginseng, also known as Withania somnifera (WS), supplementation on middle cerebral artery occlusion (MCAO) induced mitochondrial dysfunctions in experimental model of ischemic stroke. Stroke was induced in animals by occluding the middle cerebral artery, followed by reperfusion injury. Ischemia reperfusion injury resulted in increased oxidative stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 57 publications
1
17
0
1
Order By: Relevance
“…Interestingly, pre-treatment of SH-SY5Y cells with KSM-66 followed by 6-OHDA treatment was able to lower protein glutathionylation within the cells ( Figure 7 ). These results are in agreement with earlier reports on Ashwagandha extract mediated inhibition of glutathionylation formation in in vitro and in vivo studies ( Sood et al., 2018 ; Vidyashankar et al., 2014 ). It has been reported that a mechanism for Ashwagandha protection of neuronal cells was through activation of the Nrf2 pathway ( Hybertson et al., 2019 ; Priyandoko et al., 2011 ).…”
Section: Discussionsupporting
confidence: 94%
“…Interestingly, pre-treatment of SH-SY5Y cells with KSM-66 followed by 6-OHDA treatment was able to lower protein glutathionylation within the cells ( Figure 7 ). These results are in agreement with earlier reports on Ashwagandha extract mediated inhibition of glutathionylation formation in in vitro and in vivo studies ( Sood et al., 2018 ; Vidyashankar et al., 2014 ). It has been reported that a mechanism for Ashwagandha protection of neuronal cells was through activation of the Nrf2 pathway ( Hybertson et al., 2019 ; Priyandoko et al., 2011 ).…”
Section: Discussionsupporting
confidence: 94%
“…Withaferin A is a component of Withania somnifera ( ashwagandha or Indian ginseng ) ( Srivastava et al, 2020 ). W. somnifera has been used in traditional medicine as an antioxidant, antianxiety, anti-inflammatory, antibacterial, aphrodisiac, and herbal tonic for general health ( Sood et al, 2018 ). The active ingredients include withanolides, saponins, alkaloids, and steroidal lactones.…”
Section: Discussionmentioning
confidence: 99%
“…Adjunctive treatment with ashwagandha improved symptoms and stress in patients with schizophrenia, offering beneficial effects on cognitive function in patients with bipolar disorder and improves balance in patients with progressive degenerative cerebral ataxias ( Sood et al, 2018 ; Singh et al, 2021 ). It was recently shown that withanolides present in ashwagandha possess anti-COVID-19 properties , and these compounds exhibit good absorption and transport kinetics with no related mutagenic or adverse effects ( Srivastava et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The active ingredients mainly include withanolides, saponins, alkaloids, and steroidal lactones. W. somnifera is used in herbal formulations in traditional medicine possess antioxidant, anti-anxiety, anti-in ammatory, anti-bacterial, and aphrodisiac properties, etc (Sood et al, 2018). Ashwagandha has neuroprotective, cardioprotective, immunomodulating, and anti-cancer properties (Singh et al, 2021).…”
Section: Discussionmentioning
confidence: 99%